ISOLATION AND CHARACTERIZATION OF LISTERIA MONOCYTOGENES FROM SOME IRAQI MISCARRIAGE WOMEN - Hiba. H. H.,; K. K. Ghaima,; D. S. Qader, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to find out how common Listeria monocytogenes in a group of Iraqi women who had miscarriages. Also, investigates the dependability of molecular diagnosis, specifically evaluating the target hlyA gene as an alternate solution tool for identification. A total of 200 specimens comprising cervical swabs were collected from 176 women suffered from miscarriage and 24 women as control. The detection of L. monocytogenes in miscarriages women by using HiCrome™ Listeria Agar Base as both a selective and differential agar medium for quick and direct recognition of Listeria species. The biochemical tests were achieved for confirmation identification. In addition, virulence-associated genes (hlyA gene) isolates were identified using a Real-time PCR approach. Results show out of the 200 (patients and control) specimens, 176 women with miscarriages were analyzed and it was found that 117 (66.5%) specimens from abortion cases were negative for L. monocytogenes, while 59 (33.5%) specimens were positive for Listeria species. All 24 women of control give negative result. Seventy-five (32.4%) isolates from the 59 positive women showed the presence of the hlyA gene in Real-time PCR. We found that molecular diagnostic through Real-Time PCR is a quick and accurate diagnostic method that can help minimize the time it takes to start a specific treatment and track its success.